2021
DOI: 10.1002/pc.26071
|View full text |Cite
|
Sign up to set email alerts
|

Green composites based on thermoplastic starches and various natural plant fibers: Impacting parameters of the mechanical properties using machine‐learning

Abstract: Multivariate analyses on formulation and mechanical behavior of nonwoven and nonoriented natural fibers reinforced thermoplastic starch (TPS) composites were performed. Glycerol and water were considered as TPS plasticizers. Fibers composition (i.e., cellulose, hemicellulose, lignin), fibers morphology (fibers length), starch composition (i.e., amylose/amylopectin ratio) as well as the processing conditions (i.e., temperature, rotor speed, relative humidity during aging) were evaluated for their ability to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“… 36 , 8 The mechanical properties of SNFTs decreased with a decrease in the percentage of cellulose. Our analysis was consistent with the recent work of Morin et al, 9 who used machine learning to confirm the significance of the cellulose and lignin content and length of fibers on the mechanical properties of SNFTs.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“… 36 , 8 The mechanical properties of SNFTs decreased with a decrease in the percentage of cellulose. Our analysis was consistent with the recent work of Morin et al, 9 who used machine learning to confirm the significance of the cellulose and lignin content and length of fibers on the mechanical properties of SNFTs.…”
Section: Introductionsupporting
confidence: 92%
“…5,6,7,8 However, the chemical composition of the fibers, their manufacturing methods, and their morphology can be considered the most important parameters that influence the mechanical performance of thermoplastic composites reinforced with short natural fibers. 2,9,10,11,12 Table 1 presents an overview of the mechanical properties of various short natural fiber-reinforced plastic composites, considering the chemical composition of the fibers. The evaluation showed that bio-composites containing natural fibers with a high combined content of cellulose and hemicellulose exhibited the best mechanical properties (higher Young's modulus and yield stress).The fibers consist of cellulose, hemicellulose, and lignin.…”
Section: Introductionmentioning
confidence: 99%
“…The MLR model is a supervised machine learning model that examines the relationship between one target variable and two or more feature variables. 38 The model is trained by determining the coefficients with the smallest difference between the predicted and actual values of the target variable. Although the MLR is simple, fast to model and can handle large databases, it is not suitable for non-linear data.…”
Section: Mlr Modelmentioning
confidence: 99%
“…[ 5 ] Mechanical performance is superior in films and sheets with a high amylose starch content. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…performance is superior in films and sheets with a high amylose starch content. [6] Amylose chains can form more hydrogen bonds than amylopectin, which contributes to forming more vital films. As a result, amylose is often preferred for film formation over amylopectin.…”
mentioning
confidence: 99%